2014
DOI: 10.1007/s12011-014-9957-z
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure to Metals: Levels in Autopsy Tissues of Individuals Living Near a Hazardous Waste Incinerator

Abstract: The concentrations of a number of metals were determined in the brain, bone, kidney, liver, and lung of 20 autopsied subjects who had lived, at least 10 years, in the neighborhood of a hazardous waste incinerator (HWI) in Tarragona (Catalonia, Spain). Results were compared with those obtained in 1998 (baseline survey) and previous surveys (2003 and 2007). Arsenic, Be, Ni, Tl, and V showed concentrations below the corresponding detection limits in all tissues. Cadmium showed the highest levels in the kidney, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 30 publications
6
34
0
Order By: Relevance
“…These results suggest that 0.10 mM of Cr and 0.06 mM of As are concentrations to which human lung cells might be exposed, while we understand the difficulty in comparing the results for concentrations of Cr and As in human lung tissue in vivo and the results for promoted transforming activity by co-exposure to Cr and As in our experimental research in vitro. A previous study also showed that Cr level in wet lung tissue from subjects living near a hazardous waste incinerator in 2013 (12.3 mM) was about 2-fold higher (p < 0.001) than that in 1998 (6.6 mM) (Mari et al, 2014), suggesting the concentrations of heavy metals diffused from the incinerator increase in human lungs. Taken together, our results suggest that measures should be taken to prevent diffusion, especially of Cr and As, in the air through incineration of lumber debris including CCAtreated wood after the disaster.…”
Section: Biological Effects Of Co-exposure To Cr Cu and As On Human mentioning
confidence: 79%
See 1 more Smart Citation
“…These results suggest that 0.10 mM of Cr and 0.06 mM of As are concentrations to which human lung cells might be exposed, while we understand the difficulty in comparing the results for concentrations of Cr and As in human lung tissue in vivo and the results for promoted transforming activity by co-exposure to Cr and As in our experimental research in vitro. A previous study also showed that Cr level in wet lung tissue from subjects living near a hazardous waste incinerator in 2013 (12.3 mM) was about 2-fold higher (p < 0.001) than that in 1998 (6.6 mM) (Mari et al, 2014), suggesting the concentrations of heavy metals diffused from the incinerator increase in human lungs. Taken together, our results suggest that measures should be taken to prevent diffusion, especially of Cr and As, in the air through incineration of lumber debris including CCAtreated wood after the disaster.…”
Section: Biological Effects Of Co-exposure To Cr Cu and As On Human mentioning
confidence: 79%
“…Previous studies showed mean concentrations of 46.5 mM of Cr and 7.5 mM of As in dried lung tissues and mean concentrations of 4.8 mM of Cr and 1.9 mM of As in wet lung tissues (Mari et al, 2014). These results suggest that 0.10 mM of Cr and 0.06 mM of As are concentrations to which human lung cells might be exposed, while we understand the difficulty in comparing the results for concentrations of Cr and As in human lung tissue in vivo and the results for promoted transforming activity by co-exposure to Cr and As in our experimental research in vitro.…”
Section: Biological Effects Of Co-exposure To Cr Cu and As On Human mentioning
confidence: 89%
“…The content of elements in bone tissue and of some trace elements have been frequently assessed in numerous studies. [18][19][20][21][22][23] The comparison of gender-related iron concentrations showed that the lower level of the element in the knee joint of women as compared to men was in the meniscus. The iron content in the femur and tibia was found to be higher than in men.…”
Section: Discussionmentioning
confidence: 99%
“…To grade the individual CAsE, we establish BAsL intervals based on the median bone arsenic concentration reported for 160 autopsy and 92 surgical specimens (Brodziak‐Dopierała, Kwapulinski, & Kowol, ; Mari et al, ; Yoo et al, ) as well as the estimated BAsL in a number of our own patients presenting with arsenic neuropathy. BAsL can be estimated non‐invasively as osteoresorptive arsenic in two consecutive urine samples as described elsewhere (Dani, ).…”
Section: Chronic Arsenic Intoxication Diagnostic Score Methodologymentioning
confidence: 99%